IMPLEMENTATION OF NEW TECHNOLOGIES IN TRADITIONAL HANDCRAFTS: EXAMPLES FROM THE HIGHER EDUCATION (Proceedings of the International Conference on Education, 2021)
The implementation of new technologies in traditional handcrafts is being an increasingly popular interdisciplinary practice in arts, education and other aspects of life including entertainment, interior and public design. The present research explores the possibilities of the implementation of electrical and light technologies in traditional handcrafts with the purpose of providing a rich multisensory experience. The implied methodology involves practice-based research through creation of handcrafts with implementation of new technologies by the author-instructor and students in the Higher Education. Students’ handmade creations involve a wide range of media: paintings, sculptures, collage, puppets and other constructions with implemented new technologies including light effects, coding, movement sensors and renewable energy in contexts of art, education, interior and public space. The implementation of new technologies turned out to be a hands-on art-and-technology practice with multiple benefits in education. Students realised that many different aspects of the traditional handcrafts were revealed with the use of new technologies and that their implementation brings traditional handcrafts to (another) life. Furthermore, it became clear that students’ practice through the implementation of new technologies in traditional handcrafts constitutes their own preparation for applying these technologies to children’s handmade constructions and, thus, it is possible to enhance and enrich children’s creative experience. The stimulation of many senses thanks to the implementation of new technologies can also improve visual and multisensory culture, foster creativity and contribute to cultural and technological literacy. The tension between the traditional and the contemporary through the coexistence of different media proved to be a fruitful synergy making the final whole more interesting than the sum of its parts.
Keywords: art; technology; handcrafts; education; design